2012
DOI: 10.5183/jjscs.1103002_193
|View full text |Cite
|
Sign up to set email alerts
|

<b>ON INTERVAL ESTIMATION OF THE POISSON PARAMETER </b><b>IN A ZERO-TRUNCATED POISSON DISTRIBUTION </b>

Abstract: When the research outcome is counts of a rare event, Poisson distribution is a first choice to describe the population distribution under study. However in some applications, the zero count would not be observed at all. In such cases the model to be fitted to the data is a zero-truncated Poisson (ZTP) distribution. This distribution is a special case of the more general zero-modified Poisson (ZMP) distribution family. This article discusses estimation procedures for the Poisson parameter of the ZTP model. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Simulations were used to confirm the performance of the confidence interval. It was found that the coverage probabilities of the confidence interval proposed by Daidoji & Iwasaki (2012) were lower than the target probability in many cases, especially when the sample sizes were less than 50. Many techniques have been developed to estimate the functions of parameter in the distribution related to the Poisson model.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Simulations were used to confirm the performance of the confidence interval. It was found that the coverage probabilities of the confidence interval proposed by Daidoji & Iwasaki (2012) were lower than the target probability in many cases, especially when the sample sizes were less than 50. Many techniques have been developed to estimate the functions of parameter in the distribution related to the Poisson model.…”
Section: Introductionmentioning
confidence: 99%
“…We know that confidence interval which has a high coverage probability will cover the true parameter value better than that has a low coverage probability. However, as noted in Daidoji & Iwasaki (2012) little papers on interval estimation for the ZTP distribution have been shown. The confidence interval introduced in that paper is also unsatisfactory in terms of coverage probability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lambert (1992) (Lee, Stevenson, Wang and Yau (2002), Lord, Washington and Ivan (2005)) (Böhning, Dietz and Schlattmann, 2000) (Paul, Jiang, Rai and Balassoriya, 2007) Gardner, Mulvey and Shaw (1995) Daidoji and Iwasaki (2012) ( (Dempster, Laird and Rubin, 1977) ω ω…”
mentioning
confidence: 99%